A 2D, fully-coupled, hydro-mechanical, FDEM formulation for modelling fracturing processes in discontinuous, porous rock masses. (January 2017) - Lisjak, A.; Kaifosh, P.; He, L.; Tatone, B.S.A.; Mahabadi, O.K.; Grasselli, G.
Abstract: This paper presents a new, fully-coupled, hydro-mechanical (HM) formulation for a finite-discrete element method computer code. In the newly-developed, hydraulic solver, fluid flow is assumed to occur through the same triangular mesh used for the mechanical calculations. The flow of a viscous, compressible fluid is explicitly solved based on a cubic law approximation. The implementation is verified against closed-form solutions for several flow problems. The approach is then applied to a field-scale simulation of fluid injection in a jointed, porous rock mass. Results show that the proposed method can be used to obtain unique geomechanical insights into coupled HM phenomena.